Influence of Al2O3 Addition on Structure and Mechanical Properties of Borosilicate Glasses - Bruns, Sebastian; Uesbeck, Tobias; Weil, Dominik; Möncke, Doris; van Wüllen, Leo; Durst, Karsten; de Ligny, Dominique (Frontiers in Materials, 2020)
Alkali-borosilicate glasses are one of the most used types of glasses with a high technological importance. In order to optimize glasses for diverse applications, an understanding of the correlation between microscopic structure and macroscopic properties is of central interest in materials science. It has been found that the crack initiation in borosilicate glasses can be influenced by changes in network interconnectivity. In the NBS2 borosilicate glass system (74.0SiO2-20.7B2O3-4.3Na2O-1.0Al2O3 in mol%) two subnetworks are present, i.e., a silicate and a borate network. Increasing cooling rates during processing were found to improve glasses crack resistance. Simultaneously, an increase in the network interconnectivity accompanied by an increasing capacity for densification were noticed. Their individual contribution to the mechanic response, however, remained unclear. In the present study the borosilicate glasses were systematically modified by addition of up to 4.0 mol% Al2O3. Changes in the network connectivity as well as the short- and medium-range order were characterized using Raman and NMR spectroscopy. Both the Raman and the 11B NMR results show that four-fold-coordinated boron is converted into three-fold-coordination as the Al2O3 content increases. Additionally, 27Al NMR experiments show that aluminum is dominantly present in four-fold coordination. Aluminum-tetrahedra are thus charge balanced by sodium ions and incorporated into the silicate network. Finally, nanoindentation testing was employed to link the inherent glass structure and its network configuration to the mechanical glass response. It was found that the glass softens with increasing Al2O3 content, which enhances the crack resistance of the borosilicate glass.